Relation between Working in Petrol Station and Blood Hemoglobin Levels for the Filling Workers in Al-Najaf City/ Iraq - Fulath Abdul-Redah Muhsin (Indian Journal of Forensic Medicine & Toxicology, 2020)
Petrol station workers were exposed to several pollutants like air pollutants by inhalation, or skin contact with petroleum derivatives like benzene, and another port of entry. This comparative cross-sectional study was conducted to find a relationship between working in petrol stations and hemoglobin blood levels of the workers in Al- Najaf-city. The exposed worker’s group was (50 male) of petrol station workers aged 20-50 years, the years of working was (1 ?15 years) of ( ?7 h/day) that included in this study, the comparison group was 50 healthy male service and office workers aged (20-50 years) matching with the study group from alKufa Technical Institute, Al-Furat Al-Awsat Technical University. Blood samples were tested at the field by using a digitized portable device (hemochromax plus) which gave the blood hemoglobin concentrations at mg/dl of the petrol stations worker. The results of blood hemoglobin were compared between both groups. There was a highly statistically significant difference (HS) between Gas station workers and Control group at the P-value of (0.001) of Hb blood concentration levels and the mean of gas station worker and control group were (11.57 and 15.58 mg/dl) respectively. there was a highly statistically significant difference (HS) between not anemic and anemic workers at the P- value ( 0.000), and there were 47 workers (94%) out of all 50 workers had anemia after the field test. There was a statistically significant difference (HS) between Hb levels of Gas station workers and Standard Normal Hb Level at the P-value = 0.007. There were a moderate inverse negative correlated between the time of exposure in the year and blood hemoglobin levels in mg/dl at the (r = - 0.57), which mean there were decreases of blood hemoglobin levels of the worker when increases of the duration of service employment. The study concluded from all results that were finding that decreased blood hemoglobin concentration than the normal value of the petrol stations workers for all stations, which might be due to the adverse effect of the workplace pollutant on bone marrow. Attention should be given by a periodical medical assessment of all workers in the petrol stations, and Obligate the petrol stations managers for supplies all personal protective equipment for all workers.